Antimalarial activity of triterpenoids with the cucurbitane skeleton - Ramalhete, Cátia (2012)
Malaria,caused by protozoan parasites of the genus Plasmodium,is a devastating infectious disease in developing countries.One of the biggest problems that have hindered the control of malaria is the emergence and spread of drug resistant Plasmodium strains, particularly Plasmodium falciparum. In order to overcome this problem,new therapeutic agents based on new mechanisms of action or with new structures are urgently needed.Plants have been an important source of medicines against malaria. Quinine and artemisinin,two of the most important antimalarials currently in use, were derived from plants[1,2]. Momordica balsamina L(Cucurbitaceae),a vegetable used as food, has also been widely used in traditional medicine, mainly for the treatment of fever and malaria in Mozambique and SouthAfrica[3]. Continuing our search for biologically active compounds from Momordica balsamina[4,5], the aim of this work was to find out antimalarial compounds from this medicinal African plant(Fig.1).